2 Answers | Add Yours
Use substitution to solve the integral.
You may come up with the following substitution: x+1 = t.
Differentiating the equation above you will find dx: dx = dt
Write the new integral:
`int (1/t^4)*dt = int t^(-4) dt = t^(-4+1)/(-4+1) + c`
`` Replace t by x+1.
`int dx/(x+1)^4= -1/(3(x+1)^3) + c`
Integrating`1/(x+1)^4` yields`int dx/(x+1)^4= -1/(3(x+1)^3) + c.`
which will equal to (x+1)^-4
then int (1+x)^-4
inverse it back the faction like before which will give =1/-3(1+x)^3 +c
Join to answer this question
Join a community of thousands of dedicated teachers and students.Join eNotes